Potentielle Steuergrößen für das Klima Ostchinas (Sea Surface Temperature, Southern Oscillation, El Niño, Sonnenaktivität) – Analysezeitraum von 1470 bis 1990 - Wollesen, Dirk; King, Lorenz; Tong, Jiang; Jiaqi, Chen (ERDKUNDE, 1999)
The analysis of the Chinese historic time series demonstrates that the Chinese data can contribute decisively to the general understanding of the climate of the Pacific region. One result is a strong correlation of the Sea Surface Temperatures (SST) to the historic time series (r = -0,44, < 0,01), formed from documents and chronicles (1470 to 1910) as well as from annual precipitation (1911 to 1990). The SST reflects quite well the climate anomalies of El Niño and La Niña. By using the Chinese historical data it is now possible to reconstruct an El Niño/La Niña history for the last 530 years. The El Niño/La Niña time series developed here were examined with the help of the harmonic analysis. The most important result is a highly significant oscillation at 10.4 years. The periodicity of the sun activity varies between 10 and 12 years. For this reason it might be questioned to what extend the Pacific climate system is controlled by the sun activity. A further result is found by a simple correlation analysis of the SST with the annual precipitation of 81 stations. This analysis shows a spatial arrangement of the relationships, which can be divided in three parts. The result of this test is in particular a negative correlation for the northern areas of Chinas to the water temperatures of the equatorial East Pacific. Towards the south follows a zone with positive as well as negative correlation values. Finally, for the southern coast region dominates a positive relationship to the SST. A last significant result could be determined with the help of a detailed calculation method. The data base are monthly precipitation values and Sea Surface Temperatures from 1911 to 1990. The outcome of this analysis is a Pearson correlation factor of r = -0,72 for the above-mentioned parameters ( < 0,01). These results show once more the exceedingly close relationship of the Chinese precipitation to the Pacific climate system.